An Overview of the Legal, Institutional, and Regulatory Framework for Bank Insolvency. (Policy Papers; Policy Paper ;, 2009)
This study provides an overview of the legal, institutional, and regulatory framework that countries should put in place to address cases of bank insolvency. It is primarily intended to inform the work of the staffs of the International Monetary Fund (IMF) and World Bank, and to provide guidance to their member countries.